2012
DOI: 10.1111/j.1442-1984.2011.00358.x
|View full text |Cite
|
Sign up to set email alerts
|

Nematode‐induced galls in Miconia albicans: effect of host plant density and correlations with performance

Abstract: The study of nematodes parasitizing native plants plays a crucial role in understanding plant-pathogen interactions. In the present study we describe the patterns of attack by an undescribed species of Ditylenchus occurring in Miconia albicans (Melastomataceae), a widespread, native shrub from the Brazilian cerrado. We also tested the hypothesis that nematode-induced leaf galls negatively correlate to host plant performance and that gall density is a function of host plant density. We collected paired healthy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
31
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 24 publications
(37 reference statements)
3
31
0
Order By: Relevance
“…In contrast to insect galls, few ecological studies have addressed incidence of nematode galls in native species in the Neotropics. Although it seems premature to conclude that nematode-induced galls pose significant losses to plant performance, a consensus is emerging that nematode attack negatively affects plant performance (Seixas et al, 2004a, b;Santos et al, 2012;Viana et al, 2013). However, we still lack unequivocal quantitative data of the impact of nematode galls on plant performance.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In contrast to insect galls, few ecological studies have addressed incidence of nematode galls in native species in the Neotropics. Although it seems premature to conclude that nematode-induced galls pose significant losses to plant performance, a consensus is emerging that nematode attack negatively affects plant performance (Seixas et al, 2004a, b;Santos et al, 2012;Viana et al, 2013). However, we still lack unequivocal quantitative data of the impact of nematode galls on plant performance.…”
Section: Discussionmentioning
confidence: 97%
“…Miconia albicans is the host of galls induced by Ditylenchus gallaeformans (Oliveira et al 2013) (Nematoda). These nematode-induced galls occur in both leaves and reproductive structures, which potentially reduce plant productivity (Viana et al, 2013).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The symptoms and the density of the galls that were observed on M. albicans inflorescences indicate that D. gallaeformans can quite effectively control pest plants in the family Melastomataceae. Viana et al (2013) verified that M. albicans infected with Ditylenchus sp. has not only significantly shorter inflorescences and less fruit production than specimens not infected with the nematode but also severely reduced seed viability.…”
mentioning
confidence: 80%
“…Viana et al (2013) and Silveira and Oliveira (2013) reported symptoms caused by Ditylenchus sp. ; however, the identification of the species of this nematode was not performed.…”
mentioning
confidence: 99%